Proportional Hazards Model for Predictors of Type 2 Diabetes Mellitus among the Elderly - N Tumurang, Marjes; Indra Elisabet Lalangpuling (Journal of Liaquat University of Medical & Health Sciences, 2024)
OBJECTIVE: To find the prevalence and prognostic characteristics of type 2 diabetes mellitus (T2DM) in older adults. METHODOLOGY: This study's quantitative observational approach utilized the Cox proportional hazards model. This study was conducted from January to June 2024 in Manado City's urban regions. Data was collected at nearby community health centres and senior care institutions to guarantee participant accessibility and convenience. This study included older adults aged 60 or older living in urban settings. Based on power estimates, a sample size of 550 participants was chosen to guarantee adequate statistical power to identify significant correlations between predictive factors and the occurrence of T2DM. Medical examination (BMI, HbA1c and fasting plasma glucose) and structured interviews were used. The participants willing to provide informed consent were included, while exclusions included severe comorbidities and cognitive impairment. The studies were conducted using SPSS version 25. RESULTS: In the study population, T2DM was prevalent in 45% of cases. The key prognostic factors discovered included dietary habits, degree of physical activity, body mass index, and family history of Diabetes. T2DM was found to be predicted by unhealthy eating habits (HR = 1.62, 95% CI: 1.10-2.39), low physical activity (HR = 1.54, 95% CI: 1.02-2.33), high body mass index (HR = 1.87, 95% CI: 1.25-2.80), and a family history of Diabetes (HR = 2.15, 95% CI: 1.42-3.25). CONCLUSION: The high incidence of Diabetes in older adults makes it essential to intervene in diet, physical activity and weight control.